Political Positioning of the Gerindra Party and the National Awakening Party (PKB) in the 2024 Indonesian General Election - Fajri Assidiq; Diki Wahyudi (Internasional Journal of Politics and Public Policy, 2026)
This study examines the political positioning of the Great Indonesia Movement Party (Gerindra) and the National Awakening Party (PKB) in Indonesia’s 2024 General Election. Both parties represent contrasting ideological foundations and voter bases, making them important cases for analyzing contemporary party competition. Using a qualitative approach based on a literature review of academic studies, media sources, and electoral data, this research applies political marketing and positioning theory to explore how each party constructs and communicates its identity. The findings show that Gerindra adopts a nationalist-populist positioning centered on strong personal leadership, patriotism, and economic sovereignty, which effectively attracts cross-demographic support, particularly among young voters. In contrast, PKB maintains a cultural-religious positioning rooted in moderate Islamic values and strong ties to Nahdlatul Ulama (NU), resulting in a loyal but segmented electorate. Although PKB demonstrates stable electoral growth, its positioning is less competitive compared to Gerindra’s broader appeal. The study concludes that political positioning plays a crucial role in shaping voter preferences and electoral outcomes in Indonesia’s evolving democratic landscape.